Differential outcomes effect in four-year-old children - Luis J. Fuentes (Psicológica, 2003)
To date, very few studies have demonstrated the benefit of the differentialoutcomes procedure in human learning. In one of these studies (Maki,Overmier, Delos, and Gutman, 1995) there was evidence that normalchildren, ranging in age from 4 years and 6 months to 5 years and 5 months,performed better on a symbolic matching-to-sample task when they receiveddifferential outcomes following their correct responses. However, they onlyfound facilitative effects of the differential outcomes methodology in 4-yearoldchildren when the last eight trials were analyzed. In the present study, weused a similar task to that used by Maki et al. (1995) but we included a newphase for additional training. Participants, children ranging in age from 4years to 4 years and 6 months, showed a better terminal accuracy and a fasterlearning of the task across the different phases when differential outcomeswere arranged. These data indicated that additional training is not necessary tofind the differential outcomes effect in 4-year-old children.